Comparison of the effects of inhalant furosemide, oxygen therapy, and placebo in patients with acute dyspnea referred to emergency departments by EMS in various hospitals in Tehran - Mahdi Rezai; Danyal Yarahmadi; Mojde Mirkheshti; Mehrad Aghili; Reza Mosadegh; Kourosh Javdani Esfehani; Saeed Abbasi; Fatemeh Naseri Rad (International Journal of Emergency Medicine)
Abstract Background Acute dyspnea is a common presentation in emergency departments (EDs), which is one of the main complaints of the patients. There is an urgent need for an effective treatment plan for dyspnea. This study aims to compare the efficacy of inhalant furosemide, oxygen therapy, and placebo in patients with acute dyspnea referred to EDs in Tehran by Emergency Medical Services (EMS). Methods This randomized clinical trial included patients aged 18 to 75 who experienced acute dyspnea and were delivered to the ED by EMS during 2021 and 2022. Participants were randomly assigned to one of three groups: inhalant furosemide, oxygen therapy, or placebo (distilled water) which every group received the medication before entering EDs in a prehospital setting. Results The mean age of patients was 52.63 ± 20.48 years including 124 women (47.7%) and 136 men (52.3%). Our finding indicates that dyspnea intensity, heart rate, blood pressure, and oxygen saturation showed no significant differences among the groups (p-value). However, these parameters significantly improved in both the treatment and placebo groups (p-value). The mean degree of dyspnea in the furosemide group was lower than that in the other two groups, although the difference was not statistically significant. Hospitalization duration was significantly shorter in the furosemide group compared to the oxygen therapy and placebo groups. Conversely, ICU admission duration was significantly shorter in the oxygen therapy group than in the other two groups. Patient satisfaction levels did not differ significantly across groups. Conclusion The main effect of inhalant Furosemide in this study was reducing the patient’s length of hospitalization. It seems that Furosemide can have positive effects and can be used as a cure according to its low side effects, also this drug isn’t expensive and its mechanism of action, side effects, and pharmacokinetics have been shown and understood. Trial registration This study was registered with the IUMS Ethics Committee, receiving the ethical code (IR.IUMS.REC.1399.632), it was also listed in the Iranian Registry of Clinical Trails (IRCT20151003024317N12) on November the 10th, 2020.